Synergy or competition? Case heterogeneity and court performance in Polish first-instance civil and commercial courts - Bełdowski, Jarosław; Dąbroś, Łukasz; Wojciechowski, Wiktor (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: The study uses data on Polish civil and commercial courts of first instance to examine the determinants of the court output measured by the number of cases they adjudicate. Aim: Besides taking into account a caseload, number of serving judges and auxiliary court staff members, the novelty of the research is that it pays particular attention to the problem of the heterogeneity of cases on the docket which both types of courts are dealing with. Using a set of fixed effects panel data models and addressing potential endogeneity, we test whether this variation promotes court performance or, on the contrary, reduces it. Results: The results confirm that judges play a significant role in resolving cases albeit it considerably varies between distinguished type of adjudications. The auxiliary court staff members also turned out to affect court output in a different way, depending mainly on the type of cases under examination. The results indicate that there can be both synergy and competition in resolving certain types of cases. This synergy can be explained by either judicial backlash or an increase in experience in judges and support staff that makes the judicial process more time-efficient. The competition between certain types of cases may be indicative of opportunistic behaviour in some courts.